Problems and trends in the development of small and medium-sized enterprises in Ukraine - A.М. Tkachenko; A. V. Khanenko (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The article deals with entrepreneurship as one of the main spheres of the national economy and an important component of its competitiveness. The role of domestic entrepreneurship in the structural reorganization of the economy is determined. It is determined in the irreversibility of Ukraine’s entry into the European economic system. The article analyzes the opinions of financial experts on the unpreparedness of Western banks and companies to lend to Ukrainian businesses in the context of the ongoing economic crisis and military operations. The article considers and suggests that small and medium-sized business owners use modern sources of financing for their business projects, such as franchising and crowdfunding. The author defines the essence and real content of domestic entrepreneurship and its compliance with modern civilization standards. Entrepreneurship is considered in terms of its participation in the formation of political and economic relations in the country, in the search for effective legal mechanisms to ensure the comprehensive development of small and medium-sized businesses. The author establishes the connection between entrepreneurship and the increase in the number of owners of resources and means of production. This gave impetus to the corresponding formation of the middle class in society, which is the key to political and economic stability in any democratic country. Social and societal processes and their impact on the formation of small and medium-sized businesses are outlined. The influence of business on these processes is considered from the point of view of business as a social phenomenon. Amendments and additions to some laws regulating the activities of small and medium-sized enterprises are reviewed. The main directions of development of entrepreneurship in Ukraine at the present stage are determined. It is determined that the development of domestic small and medium-sized businesses is in line with global trends in the formation of a flexible market economy and a combination of both different forms of ownership and different business models.